Strategies for Interfering With Bacterial Early Stage Biofilms - Fu, Jingyuan; Zhang, Yuning; Lin, Shiyu; Zhang, Wei; Shu, Gang; Lin, Juchun; Li, Haohuan; Xu, Funeng; Tang, Huaqiao; Peng, Guangneng; Zhao, Ling; Chen, Shiqi; et al. (Frontiers in Microbiology, 2021)
Biofilm-related bacteria show high resistance to antimicrobial treatments, posing a remarkable challenge to human health. Given bacterial dormancy and high expression of efflux pumps, persistent infections caused by mature biofilms are not easy to treat, thereby driving researchers toward the discovery of many anti-biofilm molecules that can intervene in early stage biofilms formation to inhibit further development and maturity. Compared with mature biofilms, early stage biofilms have fragile structures, vigorous metabolisms, and early attached bacteria are higher susceptibility to antimicrobials. Thus, removing biofilms at the early stage has evident advantages. Many reviews on anti-biofilm compounds that prevent biofilms formation have already been done, but most of them are based on compound classifications to introduce anti-biofilm effects. This review discusses the inhibitory effects of anti-biofilm compounds on early stage biofilms formation from the perspective of the mechanisms of action, including hindering reversible adhesion, reducing extracellular polymeric substances production, interfering in the quorum sensing, and modifying cyclic di-GMP. This information can be exploited further to help researchers in designing new molecules with anti-biofilm activity.